Cancer patient experience in a nuclear medicine department: comparison between bone scintigraphy and 18F-FDG PET/CT - Grilo, Ana Monteiro (2020)
Objective: To assess the emotional impact on cancer patients undergoing Nuclear Medicine scans and identify how professionals can improve patient experience. Methods: 94 patients undergoing a Bone Scan (BS) or a Positron emission tomography/Computed Tomography (18F-FDG PET/CT) completed two Scan Experience Questionnaires and the State Anxiety Inventory (STAI-S) prior to the scan and after image acquisition. Results: Before the exam, the mean anxiety levels were higher for the BS patients compared to the 18F-FDG PET/CT group. For the post-scan STAI-S mean score, the opposite is true. Both groups experienced a reduction in levels of anxiety after the scan (BS - STAI score pre-scan = 51.75, and post-scan = 36.70; 18F-FDG PET/CT - STAI score pre-scan = 44.67, and post-scan = 38.82). The greatest anxiety factor for the BS group was the duration of the exam - 5.34 ± 2.08 (mean ± SD), while for the 18F-FDG PET/CT group it was the result - 5.40±1.80 (mean ± SD). Conclusion: Patients undergoing NM exams in an oncological context revealed significant anxiety levels prior to and after their scans. However, the BS and 18F-FDG PET/CT have different triggers. It is of extreme importance that healthcare professionals are aware of these peculiarities and adjust their procedures accordingly.